The Roles of Teacher in Implementing Independent Learning at BBC Vocational High School Medan - Dea Erianti; Yessa Ananda Wibowo; Neni Afrida Sari Harahap; Karunia Devi Frida (Universitas Negeri Medan, 2025)
This study explores the roles of teachers in implementing independent learning at BBC Vocational High School Medan. The research addresses two core questions: how teachers conceptualize their roles in fostering independent learning and how these roles are implemented in classroom practice. Using a qualitative descriptive case study approach, data were collected through classroom observations, interviews, and document analysis. Findings indicate that teachers predominantly fulfill roles as educators, motivators, planners, organizers, and evaluators. However, roles such as facilitator, mentor, and initiator are only partially implemented. The study underscores the importance of expanding teacher capacities to foster autonomy in vocational education and suggests areas for professional development to enhance independent learning practices.